QoS-as-a-Service in the Local Cloud - Lino Ferreira, Luis (2016)
10th International Workshop on Service-Oriented Cyber-Physical Systems in Converging Networked Environments (SOCNE 2016). 6, Sep, 2016. Berlin, Germany.SOCNE was held as part of ETFA 2016 that took place in Berlin, Germany on September 6-9, 2016.